Cobalt doping of α-Fe/Al2O3 catalysts for the production of hydrogen and high-quality carbon nanotubes by thermal decomposition of methane. (31st July 2020) - Torres, D.; Pinilla, J.L.; Suelves, I.
Abstract: Fe–Co/Al2 O3 catalysts were developed and tested in the catalytic decomposition of methane (CDM) for the synthesis of multi-wall carbon nanotubes (MWCNT) and the CO2 -free hydrogen production. While Fe (54.5–66.7 mol.%) is the main active phase for the carbon formation on the catalyst, Co acts as dopant aiming to improve its overall catalytic behaviour. Catalysts with Co contents of up to 18.2 M% showed the presence of α-Fe and Fe–Co crystallites with different size and lattice parameter. Fe1-x Cox alloy with bcc crystal system was identified only for Co contents of 14.0% and above, and presented a lattice constant lower than α-Fe, which would modify the carbon diffusion of the metal particle during the MWCNT growth. Co inhibited the Fe3 C formation during CDM resulting in higher carbon formations and longer activity times. This phase, shown in undoped catalysts, favored the presence of bamboo-type carbon nanotubes. Graphical abstract: Image 1 Highlights: Co-doped α-Fe/Al2 O3 catalysts are used to synthesize MWCNT by methane decomposition. Fe1-x Cox alloy is only identified for Co contents of 14.0 M% and above. Co inhibits the Fe3 C phase formation during the MWCNT growth. Fe3 C exhibits lower carbon diffusion rate and promotes the bamboo MWCNT formation.